Epistemologi Ibn Taymiyah dan Sistem Ijtihadnya dalam Kitab Majmu al-Fatawa - La Ode Ismail Ahmad; Muhammad Amri (Al-Ulum, 2019)
This paper examines Ibn Taymiyah's epistemology in the book Majmu 'al-Fatawa which contains a collection of his fatwas. The results of the discussion can be concluded that Ibn Taymiyah carried out three methods of ijtihad, ijtihad bayani, ijtihad qiyasi and ijtihad Istislahi although not comprehensively from various forms of each method. In general, Ibn Taymiyah's theory in ijtihad offers an inductive thinking method (empirical). Empiric is not only what is done and written by people, but can be in the form of daily life or natural events, but also in the form of verses and hadith. In the present era, a new method of interpreting the Koran, interpretation of mawdu'iy by collecting verses about a problem, then comprehensively understood and then concluded. It seems that this method is in line with Ibn Taymiyah's method of placing nas as empiric, not as a theory, while theory is generated from research.